PENGEMBANGAN PANGAN FUNGSIONAL BUBUR INSTAN RENDAH INDEKS GLIKEMIK BERBASIS PANGAN LOKAL - Mado, Juenita Elfunam; Rawung, Dekie; Taroreh, Mercy (Fakultas Pertanian, Universitas Sam Ratulangi, 2020)
AbstractThe purpose of this study was to analyze the nutritional content and glycemic index value of local food-based instant porridge products. The research method used was experimental research with the determination of the glycemic index using a one-shot case study design on a sample of white rats (Rattus novergicus). The results obtained in this study are the glycemic index value of instant porridge which is included in the low GI category, namely goroho plantain 31,88, baruk sago 39,43, and